Pengaruh Berat Badan terhadap Siklus Menstruasi pada Mahasiswi Semester Akhir Biologi 2020 Universitas Negeri Padang - Kurnia, Aifa; Atifah, Yusni (Lembaga Yasin AlSys, 2024)
Menstruation is a primary sexual sign that marks the period of puberty for a woman. Sooner or later to start the menstrual cycle is closely related to certain circumstances both physical and psychological states are influenced by the physical state of the woman herself, One of the factors that can interfere with the menstrual cycle is weight. The purpose of this study was to determine the relationship between body weight and the regularity of the menstrual cycle. The research method used is correlational research with a cross sectional design approach. Data was collected by distributing questionnaires with a target sample of 30 respondents. The data was analyzed using the Chi-Square test. The results of the study found that there is a relationship between the influence of weight on the menstrual cycle. The conclusion in this study that has been analyzed data tested using chi-square statistics obtained a significant value of x < 0.05 that there is a significant influence between body weight and the menstrual cycle.